MEMBUDAYAKAN LITERASI DIGITAL PADA ANAK SEKOLAH DASAR DI DESA KALIJAGA KECAMATAN AIKMEL LOMBOK TIMUR - Alwan, Muhammad; Sunarya Herawati, Nita; zarkasi, Taqiudin (Jurnal Empowerment: Jurnal Pengabdian pada Masyarakat, 2021)
The emergence of covid-19 has a significant impact on the world of education, especially in the teaching and learning process. The government through the Minister of Education appealed for the implementation of the teaching and learning process to be carried out with Online learning. Based on the appeal, SDN 2 Kalijaga until now is still carried out learning activities through online, Then teaching and learning activities are carried out with digital devices such as smartphones and laptops. However, based on observations on the ground digital devices such as smartphones are not used wisely, smartphones are used for online games and tiktok. This is due to students' lack of digital literacy about utilization, use, and impact. Therefore, devotional activities focused on cultivating digital literacy in elementary school children in Kalijaga village with socialization and mentoring methods to students of SDN 2 Kalijaga. The results of the devotion showed that the role of teachers and parents is very important to direct and control the use of smartphones. Furthermore, students' understanding and skills in finding useful content for lessons in school are seen to increase after socialization and mentoring.